2017
DOI: 10.1177/1357633x17695172
|View full text |Cite
|
Sign up to set email alerts
|

Parental evaluation of a telemonitoring service for children with Type 1 Diabetes

Abstract: Introduction In the past years, we developed a telemonitoring service for young patients affected by Type 1 Diabetes. The service provides data to the clinical staff and offers an important tool to the parents, that are able to oversee in real time their children. The aim of this work was to analyze the parents' perceived usefulness of the service. Methods The service was tested by the parents of 31 children enrolled in a seven-day clinical trial during a summer camp. To study the parents' perception we propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…The final list of articles showed that the Telehealth Usability Questionnaire (TUQ) (n = 10, 19%) [10][11][12][13][14][15][16][17][18][19] and Telemedicine Satisfaction Questionnaire (TSQ) (n = 7, 13%) [20][21][22][23][24][25][26] were the most commonly used. Then, the Service User Technology Acceptability Questionnaire (SUTAQ) (n = 3, 5.5%) [27][28][29], the Client Satisfaction Questionnaire (CSQ) (n = 3, 5.5%) [30][31][32], the Questionnaire for User Interaction Satisfaction (QUIS) (n = 3, 5.5%) [33][34][35], the System Usability Scale (SUS) questionnaire (n = 3, 5.5%) [36][37][38], the Patient Satisfaction Questionnaire (PSQ) (n = 3, 5.5%) [22,39,40], the Telemedicine Satisfaction and Usefulness Questionnaire (TSUQ) (n = 2, 3.5%) [41,42], the Patient Assessment of Communication during Telemedicine (PACT) questionnaire (n = 2, 3.5%) [43,44], the Post Study System Usability Questionnaire (PSSUQ) (n = 2, 3.5%) [19,45] and the Technology Acceptance Model (TAM) (n = 2, 3.5%) [46,47] were the most used questionnaires, respectively.…”
Section: Evaluation Questionnairementioning
confidence: 99%
“…The final list of articles showed that the Telehealth Usability Questionnaire (TUQ) (n = 10, 19%) [10][11][12][13][14][15][16][17][18][19] and Telemedicine Satisfaction Questionnaire (TSQ) (n = 7, 13%) [20][21][22][23][24][25][26] were the most commonly used. Then, the Service User Technology Acceptability Questionnaire (SUTAQ) (n = 3, 5.5%) [27][28][29], the Client Satisfaction Questionnaire (CSQ) (n = 3, 5.5%) [30][31][32], the Questionnaire for User Interaction Satisfaction (QUIS) (n = 3, 5.5%) [33][34][35], the System Usability Scale (SUS) questionnaire (n = 3, 5.5%) [36][37][38], the Patient Satisfaction Questionnaire (PSQ) (n = 3, 5.5%) [22,39,40], the Telemedicine Satisfaction and Usefulness Questionnaire (TSUQ) (n = 2, 3.5%) [41,42], the Patient Assessment of Communication during Telemedicine (PACT) questionnaire (n = 2, 3.5%) [43,44], the Post Study System Usability Questionnaire (PSSUQ) (n = 2, 3.5%) [19,45] and the Technology Acceptance Model (TAM) (n = 2, 3.5%) [46,47] were the most used questionnaires, respectively.…”
Section: Evaluation Questionnairementioning
confidence: 99%
“…This system takes input from continuous activity monitoring devices (smartwatch or health band), smart devices that are used several times a day (smart scale, blood pressure monitor and blood sugar). Similar systems have been proposed [52][53][54] but a truly functional system is not yet available [55].…”
Section: Pregnancy Monitoring Systemsmentioning
confidence: 99%
“…For parents of T1D children, leaving their child at camp is often anxiety-provoking, especially when losing the ability to view the child's glucose trends in real time. Parents who can continue to monitor their child's glucose data remotely have improved moods and quality of life in comparison to those who lost access while their child is at camp (Losiouk et al, 2018).…”
Section: Remote Monitoringmentioning
confidence: 99%